Redes interdiscursivas e convergência de mídias: uma análise de Brilho Eterno de uma Mente Sem Lembranças - Mestriner, Rogério Secomandi (Universidade Federal de São Carlos, 2011)
With digital media's broad dissemination towards society, confirmed by the market expansion of electronic games and the growing digital inclusion due to Web 2.0 advances and mobile telephony, the audiovisual expression transforms itself in meaningful ways, having its effect noticed mainly at the structure of many films, such as Eternal Sunshine of the Spotless Mind (EUA, 2004), directed by Michel Gondry. This study intends to elaborate how the incorporation of certain specificities of digital media which can be seen as an actual cinematographic tendency, analyzing some of earlier works from this director to point out his manners towards the virtual world and sort it out his unique vision in an authorial and consistent body of work. We‟re interested in studying specifically the convergence process between cinematographic narrative and digital media, starting by the analysis of multilinear structures that illustrate this process. The final objective is to cast new lights over this new standard of audiovisual entertainment that rises with the coming of digital media.
Keywords: Cinema americano (Francês, inglês, etc); Cinema contemporâneo; Mídia digital; Linguagem cinematográfica; Contemporary cinema; Digital media; Michel Gondry; Cyberpunk; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA